A contextualização no ensino de Física e sua ocorrência nos processos de avaliação da Educação Básica - Sampaio, Felipe de Macedo (2022)
The present work aims to analyze how the contextualization developed by Physics teachers of High School and/or the final years of Elementary School is present in the assessments developed by them, to identify eventual training needs of these teachers, for the improvement of their assessment processes. The aim is to have a broad view of the teachers' practice, which allows identifying the multiple factors that influence their ways of evaluating and which points in the educational process should be prioritized in training activities on the topics discussed here. Thus, in addition to verifying the form and frequency that contextualization occurs in the assessment instruments developed by these teachers, the research also investigates their conceptions on the subject and the strategies adopted to contextualize the instruction moments. The study has the participation of five educators, all graduated in Physics from the University of São Paulo (USP), whose speeches, obtained in semi-structured interviews, and assessment instruments, mostly written tests, are analyzed, according to classifications of types of contextualization and context functions developed for this work. The results obtained show that all participants have some knowledge of the subject and show evidence of having discussed or previously reflected on the practice of contextualizing. Of the concepts presented, the most frequent are contextualization as a tool to promote student motivation and contextualization as a way of establishing connections between different knowledge, prior or not, making the new information better integrated into the cognitive structures of the students. Only one of the participants showed, indirectly, that he considers the context a knowledge of its own value, which goes beyond the promotion of physics learning. It indicates that this conception is infrequent among educators. It is also verified that all participants value, to a greater or lesser degree, the practice of contextualization, but intuition is what seems to determine, in most cases, the choice of strategies and the moments of the classes in which it will be carried out. In the field of Evaluation, the results show that the occurrence and the types of contexts used by the teachers in their assessments are mainly related to their conceptions about contextualization, and the subject of Physics being evaluated is not very relevant